Alumina/zirconia composites toughened by the addition of graphene flakes. Issue 13 (September 2017) - Boniecki, Marek; Gołębiewski, Przemysław; Wesołowski, Władysław; Woluntarski, Michał; Piątkowska, Anna; Romaniec, Magdalena; Ciepielewski, Paweł; Krzyżak, Konrad
Abstract: The effect of added graphene flakes on the mechanical properties of a composite containing 20 wt% Al2 O3 and 80 wt% ZrO2 (stab. 3 mol% Y2 O3 ) was studied. To obtain samples, a commercial ceramic powder produced by Tosoh (Japan), and graphene oxide (GO) made at the Institute of Electronic Materials Technology (Poland) were used. The obtained composites were based on aqueous mixtures of both components. After drying, they were sintered in an uniaxial pressure (HP) furnace. The composites contained from 0% to 3% of GO by weight. Results showed the influence of GO content i.e. fracture toughness has a maximum for 0.02% GO (increase by 42% in comparison to GO-free matrix) and afterwards decreased, strength decreased in the whole GO content range. Young's modulus and Vickers hardness remained constant up to 0.2% GO, and then decreased.